2001
DOI: 10.1007/s007050170191
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the RNA-dependent RNA polymerase from Rabbit hemorrhagic disease virus produced in Escherichia coli

Abstract: All positive-strand RNA viruses encode a RNA-dependent RNA polymerase which in most cases has been only identified on the basis of its sequence conservation. Catalytic activity has been experimentally demonstrated in only a handful of these viral proteins, including that from Rabbit hemorrhagic disease virus. Studies from our laboratory have reported that RHDV RNA polymerase produced in Escherichia coli was enzymatically active showing poly(A)-dependent poly(U) polymerase as well as RNA polymerase activity on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…To further exclude the possibility that a copy-back mechanism is used by protein A, we designed templates, (Ϫ)-RNA1(1-100) and (Ϫ)-RNA1(1-100)pA, in which the 3Ј-OHs were oxidized. The oxidized 3Ј-OH cannot be used to add extra nucleotides for oligonucleotide elongation and thus would completely block RNA synthesis via a copy-back mechanism (10,11,43). Our results showed that the templates with oxidized 3Ј-OH exhibited the same ability to initiate RNA synthesis (Fig.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…To further exclude the possibility that a copy-back mechanism is used by protein A, we designed templates, (Ϫ)-RNA1(1-100) and (Ϫ)-RNA1(1-100)pA, in which the 3Ј-OHs were oxidized. The oxidized 3Ј-OH cannot be used to add extra nucleotides for oligonucleotide elongation and thus would completely block RNA synthesis via a copy-back mechanism (10,11,43). Our results showed that the templates with oxidized 3Ј-OH exhibited the same ability to initiate RNA synthesis (Fig.…”
Section: Resultssupporting
confidence: 60%
“…10D, lanes 6 -8). On the other hand, (Ϫ)-RNA1(3-30), but not (Ϫ)-RNA1 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) or (Ϫ)-RNA1(3-10), was required for the TNTase activity (Fig. 10D, lanes 3-5).…”
Section: Cis-acting Elements At the 3ј-end Of Rna1 Govern The Rdrp Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The de novo initiation mechanism is primer-independent, and RdRPs do not require primer, but normally synthesize dinucleotides as the starting nucleotides on the 3′-end of RNA templates for adding next nucleotides [60], [61]. On the other hand, the primer-dependent initiation mechanism requires the involvement of a primer, which could be an oligonucleotide or a protein [33], [34], [35], [36]. For example, rabbit hemorrhagic disease virus and hepatitis C virus, both of which are (+)-RNA viruses, use RNA primers for the synthesis initiation of their RNA genome [33], [34], [35], while picornaviruses use a uridylylated form of the VPg protein (also named as nonstructural protein 3B) as primer for the synthesis of both (+)- and (−)-RNAs [36].…”
Section: Discussionmentioning
confidence: 99%
“…So far, viral RdRPs have been reported to employ two principally distinct mechanisms for RNA synthesis initiation [31], [32], including primer-dependent and primer-independent ( de novo ) initiation. The primer-dependent initiation of RNA synthesis requires the involvement of either an oligonucleotide or a protein primer [33], [34], [35], [36], while the de novo initiation does not require primer, but uses the starting nucleotide to provide the 3′ hydroxyl group (3′-OH) for adding the next nucleotide. In the case of de novo initiation, RNA synthesis can be initiated at the terminal or an internal site of the template RNA [28], [29], [31], [37], [38].…”
Section: Introductionmentioning
confidence: 99%